Design and Build a Prototype Assembly System Based on Dobot Magician Robot - Tugino; Muh. Harits Al Hammam; Mohammad Arsyad; Subardi (ReTII, 2022)
The assembly system is one of the systems that is widely used in industry including the assembly system of cars, motorcycles, industrial components and others. Some industries still use manual systems, so human labor is still needed so that worker errors can cause damage to goods and delay time, causing losses for the company. Therefore, an assembly system based on a dobot magician robot was created as a substitute for human workers. The prototype of the assembly system based on the dobot magician robot uses DobotStudio as its programming software and uses sensors as color detectors on goods, photoelectric sensors as goods detectors to turn on and off conveyors, and conveyors as goods carriers. The control system of this assembly robot prototype consists of 4 dobot magician robots, 5 photoelectric sensors, 2 conveyors, and 2 end effector suction cups. The prototype of the assembly robot based on the Dobot Magician robot that has been made has been able to work well. Robots can attach a miniature car frame which is a process in the assembly system.